EFEKTIVITAS MODEL EXPLICIT INSTRUCTION DALAM KETERAMPILAN VOKASIONAL PEMBUATAN KEY HOLDER KAYU PADA SISWA TUNAGRAHITA DI SKH NEGERI 01 PANDEGLANG (Studi Eksperimen dengan Pre Test Post Test pada Siswa Tunagrahita Di SKh Negeri 01 Pandeglang) - Ovi Rizal Mustaqim; Dedi Mulia; Sayidatul Maslahah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effectiveness of applying the Explicit Instruction model in improving vocational skills in making wooden key holders for students with intellectual disabilities at SKh Negeri 01 Pandeglang. The research method used was an experimental method with a One Group Pretest-Posttest Design involving five tenth-grade students as research subjects. The instrument used was an observation sheet for the vocational skill of making wooden key holders, which had been tested for validity and reliability. The study was conducted in three stages, namely pretest, treatment, and posttest, through the implementation of Explicit Instruction learning steps, including orientation, demonstration, guided practice, understanding check, and independent practice. Data analysis using the Wilcoxon test showed that the calculated T value (Tₕitung) was 15 and the table T value (Tₜabel) was 0 at a significance level of 0.05 with N = 5, thus H₀ was rejected and H₁ was accepted. These results indicate that the implementation of the Explicit Instruction model has a significant effect on improving students’ vocational skills in making wooden key holders. Students demonstrated progress in using tools, following work procedures correctly, and producing neat and well-designed products. Therefore, the Explicit Instruction model is proven to be effective in vocational learning for students with intellectual disabilities, as it enhances practical skills, accuracy, independence, and provides a concrete and systematic learning experience.